Philippine business and transfer taxes (principles, law and problems) : a new approach - Reyes, Virgilio D. ([Place of publication not identifed] : [publisher not identified], 2004)
The purpose of this book is to provide material for easy reading and understanding of the principles and laws on taxation of estate, gifts and business.
Part I: Transfer taxes -- Chapter 1. Basic concepts of successions -- Chapter 2. Gross estate -- Chapter 3. Deductions from the gross estate -- Chapter 4. Estate tax -- Chapter 5. Net taxable estate and estate tax -- Chapter 6. The conjugal partnership of gains and the estate tax -- Chapter 7. The absolute community of property and the estate tax -- Chapter 8. Net taxable estate and net distributable estate -- Chapter 9. Estate tax credit -- Chapter 10. Estate tax administrative provisions -- Chapter 11. Basic concepts of donations -- Chapter 12. Net gifts and Donor's tax -- Chapter 13. Donor's tax: Return, Payment and tax credit -- Part II: Business Taxes -- Chapter 14. Introduction to business taxes -- Chapter 15. Value-added tax on sale of goods and properties -- Chapter 16.Value-added tax on sale of services -- Chapter 17. Common VAT Rules on sale of goods or properties and of services -- Chapter 18. Value-added tax on importation -- Chapter 19. Percentage taxes 102 -- Chapter 20. Excise taxes -- Chapter 21. Documentary stamp taxes -- Chapter 22. Community tax -- Part III: Tax remedies -- Chapter 23. Tax remedies.
Philippine business and transfer taxes (principles, law and problems) :, Philippine
Keywords: BUSINESS TAX -- LAW -- PHILIPPINES